Erratum: Hubungan Kekuatan Lengan, Koordinasi Mata Tangan, Dan Fleksibilitas terhadap Keterampilan Forehand Drive - Rizki Ridha Kusuma (STKIP Muhammadiyah Kuningan, 2020)
Correction to: JUARA: Jurnal Olahraga This corrects the article DOI: https://doi.org/10.33222/juara.v4i2.546 This article was originally published using English metadata in the article title and this is our fault. but now the article metadata has been changed in Indonesian and appears correctly in the current article.